MINDO/3 Evaluation of Oxidation Numbers in Some Trisubstituted Benzens - Tripathi, R N; Yadav, J S; Singh, O P (Tribhuvan University Journal, 2011)
Available with fulltext. Key words: Mindo/3 Evaluation; Trisubstituted Benzens; Semi-empirical bond Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 91-94 Uploaded date: 29 April, 2011